- EFFECT OF SEASON ON SOME HEMATOLOGICAL, BIOCHEMICAL AND SOME HORMONE OF LOCAL IRAQI BLACK FEMALE GOATS - Waleed Y. Kasim; Abd-Alkareem A. Babe; Murtada F. AL-Hellou (Basrah Journal of Veterinary Research)
This study was conducted at animal farm / Collage of Agriculture, Basrah University, during the period from April to December . A total of 8 blood samples were taken from dry female goats at (2.5-3.5) years old during first day of April , July , October , December months .The aim of this study to evaluate the effect months of year on blood (WBC , RBC, PCV and Hb) and biochemical parameters (Fe , Phosphate, Albumin, Total protein, Cholesterol and Glucose in addition to some hormones like Estrogen and thyroxin. The present study resulted that there were significant (P